Childcare Subsidy Enrollment Income Generosity and Child Maltreatment - J. Bart Klika; Kathryn Maguire-Jack; Megan Feely; William Schneider; Garrett T. Pace; Whitney Rostad; Catherine A. Murphy; Melissa T. Merrick (MDPI AG, 2022)
In the United States, childcare subsidies are available to low-income working parents to assist with the cost of childcare. The subsidies are provided as block grants to states, which allows for a great deal of flexibility in the specific policies guiding their distribution. Prior research has found a protective link between childcare subsidies and child maltreatment, but the variations in policies have been much less explored. The current study used longitudinal administrative child welfare data from 10 years (2009-2019) linked with state policies regarding the income eligibility requirements of states to examine the impact of these policies on child abuse and neglect among young children (0-5); early school-age children (6-12), and older children (13-17). Using multiple regression and controlling for state demographic characteristics, the study found that more generous policies surrounding income eligibility were related to lower rates of child abuse and neglect investigations at the state level.